Analysis of fucoxanthin content and purification of all-trans-fucoxanthin from turbinaria turbinata and sargassum plagyophyllum by SiO2 open column chromatography and reversed phase-HPLC - Jaswir, Irwandi; Noviendri, Dedi; Mohd. Salleh, Hamzah; Bakhtiar, M. Taher; Miyashita, Kazuo; M. Ramli, Nazaruddin (Taylor & Francis Group, 2013)
Reversed phase-high performance liquid chromatography (RP-HPLC) was used to analyze fucoxanthin content of two species of Malaysian brown seaweeds, Turbinaria turbinate andSargassum plagyophyllum. The fucoxanthin contents of T. turbinata, and S. plagyophyllum were 0.59 ± 0.08 and 0.71 ± 0.01 mg/g dry-weight, respectively. Ultraviolet spectrum of fucoxanthin showed the maximum absorbance at 450 nm. Furthermore, the HPLC chromatograms of purified all-trans-fucoxanthin from showed one major peak with a retention time of 7.8 minutes.